Repeated linear and quadrangular sprint as a function of anaerobic power - Almansba, R.; Boucher, V. G.; Parent, A. A.; Comtois, A. S. (The Journal of Strength and Conditioning Research, 2019)
This investigation aims to study in U17 soccer players the relationships among performance indices of linear or quadrangular (square shape) repeated-sprint bouts (RSBs) and leg muscular power measured with the Wingate test and the squat jump. Seventeen athletes were recruited. Participants were 16 ± 0.35 years old and had a body mass of 66.5 ± 8.69 kg and a height of 175 ± 0.05 cm. All participants performed linear or quadrangular RSBs, the Wingate test, and a vertical jump test. The mean fast linear sprint time was strongly correlated (p < 0.01) with the force and power measured with the vertical jump test (r = -0.68 and -0.75, respectively), whereas the mean linear RSB was weakly correlated with the peak power and fatigue index measured by the Wingate test (r = -0.54 and -0.56, respectively). There was a correlation between quadrangular RSBs performance indices and both Wingate and vertical jump parameters. In addition, there were no correlations (p > 0.05) between indices of the linear RSBs (decrement index, average, and fastest times) and quadrangular RSBs. Moreover, physiological and perceptual responses were significantly higher (p < 0.01) with quadrangular RSBs compared with linear RSBs. These results indicate that the Wingate test and the vertical jump test can be used as a substitute for repeated-sprint performance time. Finally, however, the repeated sprints with or without direction changes are 2 different motor abilities that should be trained independently of one another.